OUTCOME OF PRIMARY PERCUTANEOUS CORONARY INTERVENTION IN PATIENTS WITH ACUTE ST-SEGMENT ELEVATION MYOCARDIAL INFARCTION ARRIVING IN ARMY CARDIAC CENTER LAHORE - Shahzad, Khurram; Ali, Jahanzab; Ahmad, Ayaz; Usman, Ahmad; Rashdi, Amna; Shafiq, Faisal (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate the feasibility and outcomes of primary percutaneous coronary intervention (PCI) as a mode of treatment in acute ST segment elevation myocardial infarction (STEMI).Study Design: Descriptive cross sectional study.Place and Duration of Study: The study was conducted in Army Cardiac Center Lahore, from Nov 2019 to Feb 2020.Methodology: All patients diagnosed as acute ST-segment elevation myocardial infarction during the study period were offered primary percutaneous coronary intervention among treatment options. Patients who chose primary percutaneous coronary intervention were included in the study. Informed consent was taken. Patient demographics, risk factors, time variables, procedural characteristics and in-hospital adverse events were evaluated.Results: On admission, Out of 50, 30 (60%) of the patients were current smokers, 25 (50%) were hypertensive, 22 (44%) were diabetic, and 1 (2%) had cardiogenic shock. The mean time from symptom onset to hospital arrival was 5 hours and the mean door-to-balloon time was 34 minutes. Culprit coronary artery was the left anterior descending artery (LAD) in 56% cases and multi-vessel disease was present in 38% cases. Primary percutaneous coronary intervention involved balloon dilatation (2%) and stent implantation (98%). The incidence of postprocedural angiographic no-reflow was 0%. All-cause mortality was 1%.Conclusion: This study has shown efficiency, feasibility and safety in performing of primary percutaneous coronary intervention with excellent outcomes in Army Cardiac Center Lahore. In order to further improve its outcomes, our goal should be to decrease reperfusion time which can be achieved by reducing patient delay, increasing public awareness and improving the management of first medical contact.